Physical Status Relationship American Society of Anesthesia (ASA) with Time to Achieve Bromage Score 2 in Spinal Anesthesia Patients in the IBS Recovery Room of Dr Iskak Tulungagung Hospital - Novita Ana Anggraini; Annisa Ary Saifutri; Nurma Afiani; Rahmania Ambarika (Universitas STRADA Indonesia, 2025)
Background: The American Society of Anesthesiologists (ASA) Physical Status classification is used to assess a patient’s overall health and predict potential complications related to spinal anesthesia. The Bromage score is commonly used to evaluate motor block recovery following spinal anesthesia, with the achievement of Bromage score 2 indicating partial motor function return. Purpose: This study aimed to analyze the relationship between ASA physical status and the time required to achieve Bromage score 2 in patients undergoing spinal anesthesia in the recovery room of Dr. Iskak Tulungagung Hospital. Methods: This research employed a cross-sectional design. The study population included all spinal anesthesia patients in the hospital’s recovery room, totaling 250 individuals. A sample of 38 respondents was selected using simple random sampling. Data were collected using observation sheets and analyzed with the Spearman Rho test at a 95% confidence level (α = 0.05). Results: The results showed that the majority of respondents (57.9%) had an ASA status of 2, and most (60.5%) achieved Bromage score 2 within 120–149 minutes. Statistical analysis revealed a p-value of 0.017 (<0.05), indicating a significant relationship between ASA physical status and time to achieve Bromage score 2. Conclusion: Higher ASA classifications are associated with more severe systemic conditions, which may slow the body's response to anesthetic drugs, resulting in a longer time to reach motor recovery.